The Vital Role Of Green Human Resource Management In Building Sustainable Organizations: A Patagonia Case Study - Benmoussa Mohammed (جامعة الوادي University Of Eloued, 2024)
This article comprehensively examines green human resource management (GHRM) and its critical role in developing sustainable organisations. GHRM leverages human resource systems to achieve environmental sustainability goals and develop green workforces. The article outlines the concept, theoretical foundations, and key dimensions of GHRM, encompassing recruitment, training, performance management, motivation, and retention. It reviews extensive empirical research demonstrating GHRM's positive impacts on sustainability outcomes like environmental performance, green behaviours, capabilities, and reputation. Significant implementation challenges include a lack of leadership commitment, narrow HR role perceptions, and misalignment with strategy. Case analysis of Patagonia highlights real-world GHRM practices. Theoretical, empirical, and practical implications are considered, emphasising GHRM's multifaceted benefits but the need for further rigorous, context-sensitive research. In conclusion, the article establishes GHRM as a vital, emerging approach for aligning human capital with sustainability, warranting ongoing investigation and application.
Keywords: Green human resource management GRHM; Environmental sustainability; GRHM practices; Patagonia